Pemanfaatan Media Massa oleh PT. Bina Mahasiswa Indonesia sebagai Stategi Pemasaran Liga Mahasiswa (LIMA) - S.B.U, Mahardono; Hidayah, Taufiq; -, Sugiarto (Media Ilmu Keolahragaan Indonesia, 2013)
The goal of this research is to describe the process of mass media usage done by LIMA in the strategy used to Liga Mahasiswa market. The method used in this research is interview and observation, and the technical documentation is case study. The result in this research shows that the mass media usage formulated by LIMA as a marketing strategy to spread out a sport event is very effective and innovative as so many explorations can be made. In the usage of media, LIMA take advantage of print media, electronic or online. One of the local media in place of activities take place for example the local media in Jakarta such as: JakTv, TraxFm, Golf Diggest and other media that contains the Mahaka Media Group and local media than in Jakarta. LIMA take advantage of the mass media which make a MOU (Memorandum Of Understanding) as one way to cooperate Furthermore, mass media is willing to cooperate with LIMA. Based on the results of such research, it can be concluded that in addition to holding the event, five hold social events with the help of the mass media in order to be published. Currently, events arranged by LIMA are developing.